2003
DOI: 10.1097/00001756-200306110-00014
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional structure and survival of newly formed blood vessels after focal cerebral ischemia

Abstract: Penumbra tissue becomes highly angiogenic after ischaemic stroke in man, and the re-establishment of a functional vasculature might be beneficial to patients. Unilateral ischaemia was induced in male Sprague-Dawley rats by permanent occlusion of the distal left middle cerebral artery (MCAO). Animals with stroke were kept alive for 1, 7, 14, 21 or 28 days after which time they were terminally anaesthetized. Vascular casts of infarcted areas, analyzed by scanning electron microscopy demonstrated that radially ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 32 publications
5
47
0
4
Order By: Relevance
“…Our finding is also consistent with early reports that CD34 þ cells selectively homed to the sites of angiogenesis, become fully integrated in the microvascular endothelium, and differentiate into mature endothelial cells (Krupinski et al, 2003;Morris et al, 2003). In addition to physical lining of vessel wall, the new endothelial cells have a significant stimulatory effect on the formation of new capillary (Zhang et al, 2002;Morris et al, 2003;Rookmaaker et al, 2005).…”
Section: Cd34 + Cells and Trauma Angiogenesis 1341 Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding is also consistent with early reports that CD34 þ cells selectively homed to the sites of angiogenesis, become fully integrated in the microvascular endothelium, and differentiate into mature endothelial cells (Krupinski et al, 2003;Morris et al, 2003). In addition to physical lining of vessel wall, the new endothelial cells have a significant stimulatory effect on the formation of new capillary (Zhang et al, 2002;Morris et al, 2003;Rookmaaker et al, 2005).…”
Section: Cd34 + Cells and Trauma Angiogenesis 1341 Discussionsupporting
confidence: 92%
“…The cells eventually home to the site of injured tissue (Beck et al, 2003;Assmus et al, 2006) to initiate and propagate angiogenesis (Krupinski et al, 2003;Morris et al, 2003). As a result, the levels of CD34 þ cells in peripheral blood and injured tissue could be considered to reliably indicate the rate and extent of tissue repair.…”
mentioning
confidence: 99%
“…30,31 Hence, VEGF monotherapy has garnered much attention as a formidable therapeutic avenue after stroke. [32][33][34] One of the first studies of VEGF in ischemic stroke showed that mRNA and protein of VEGF 165 VEGF 189 and the receptor flk-1 were found to be upregulated in human post-mortem brain. 35 In rodent models of stroke, an intra-cerebroventricular injection of VEGF via osmotic pump, starting 24 hours after onset of focal cerebral ischemia, the stimulation of angiogenesis coincided with a reduction of infarct volume.…”
Section: Vascular Endothelial Growth Factor Therapymentioning
confidence: 99%
“…To date, diverse studies have been conducted with the aim of finding substances that can induce angiogenesis, since the possibilities of clinical application of these substances in myocardial vascularity and the central nervous system are extensive, after injury or ischemia, partial replacement of large arteries, and even in wound healing (Krupinski et al, 2003;Slevin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%